Washback of English Proficiency Test in Classroom Activities at National University of Arts Education - Hoa, Dinh Thi Phuong (VNU Journal of Science: Education Research, 2020)
A study in Vietnam concerning the effects of The Vietnam Six-levels of Foreign Language Proficiency Framework, specially English Proficiency Tests for graduates, on classroom teaching and learning activities are reported. The study explores the phenomenon of washback or backwash, the influences of testing on 9 teachers and 679 non-English major students. It is cited as the only known research investigating washback in language education through classroom observation. The study was conducted at National University of Art Education, and combined classroom observations with data from interview, questionaire responses and document analysis to determine whether washback exist, to what degree it operates, and whether it is a positive or negative force in this educational context. The insights from the findings indicate that washback of English Proficiency Tests for graduates occurred in both positive and negative forms, to some degree, in teaching and learing  content, methods and styles. Evidence of washback, both positive and negative, on the way teachers design tests was also found. This should help Vietnamese educators to prepare favourable conditions for enhancing the benificial washback of EPT. The findings have contributed to the knowledge of a nature of washback and consequently opened a new understanding to recognize the dissimilar levels of washback. further research is recommended.